Peran Kepala Madrasah terhadap KegiatanKeagamaan di Mtss Raudhatul Jannah Kota Baru - Vicko Wahyu Adji Pradana; Muhammad Ragil; Muhram Muhram; Yuswantoro Satria Tama; Alfianda Ajhar (Journal Of Administration and Educational Management (ALIGNMENT), 2026)
This study aims to describe and analyze the role of the madrasah principal in religious activities at MTsS Raudhatul Jannah Kotabaru, including aspects of planning, implementation, supervision, evaluation, factors influencing the implementation of religious activities, and their impact on the formation of students' religious character. The research method used was a qualitative approach with a descriptive approach. Data were obtained through interviews, observations, and documentation involving the madrasah principal, teachers, administrative staff, and students. Data analysis was conducted qualitatively through the stages of editing, classification, data presentation, and inductive conclusion drawing. The results indicate that the madrasah principal plays a very strategic role in the implementation of religious activities through establishing a vision and mission oriented towards the formation of religious character, developing a religious activity program, providing moral and material support, and implementing ongoing monitoring and evaluation. The implementation of religious activities is influenced by internal factors such as students' religious motivation, discipline, and coordination among madrasah members, as well as external factors such as support from teachers, parents, the community, and the availability of supporting facilities. Congregational Dzuhur and Dhuha prayers have a positive impact on improving students' discipline, responsibility, togetherness, and character development. The conclusion of this study indicates that the role of the madrasah principal is crucial to the success of religious activities in shaping students' religious character through sound planning, ongoing support, and an effective monitoring and evaluation system.   Keywords: Evaluation, Religious Activities, Religious Character, Leadership